Art explosion 800,000 : with printed image catalog. (Calabasas : Nova Development Corp., 2004)
Windows XP, 2000, ME, 98.
Add style to flyers, greeting cards, newsletters, invitations and more with 800,000+ images.
Keywords: Interactive multimedia; CD-ROMs.; Clip art -- CD-ROMs.; Computer fonts -- CD-ROMs.